Frontispiece: Exploring Structure and Function of Redox Intermediates in [NiFe]‐Hydrogenases by an Advanced Experimental Approach for Solvated, Lyophilized and Crystallized Metalloenzymes. Issue 29 (5th July 2021) - Lorent, Christian; Pelmenschikov, Vladimir; Frielingsdorf, Stefan; Schoknecht, Janna; Caserta, Giorgio; Yoda, Yoshitaka; Wang, Hongxin; Tamasaku, Kenji; Lenz, Oliver; Cramer, Stephen P.; Horch, Marius; Lauterbach, Lars; et al.
Abstract : Metalloenzymes In their Research Article on page 15854, Christian Lorent, Marius Horch, Lars Lauterbach, Ingo Zebger et al. explore redox intermediates of [NiFe]‐hydrogenases by an advanced experimental approach for solvated, lyophilized, and crystallized metalloenzymes.